2000
DOI: 10.1128/jb.182.5.1383-1389.2000
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Range and Genetic Analysis of Acinetobacter Vanillate Demethylase

Abstract: An Acinetobacter sp. genetic screen was used to probe structure-function relationships in vanillate demethylase, a two-component monooxygenase. Mutants with null, leaky, and heat-sensitive phenotypes were isolated. Missense mutations tended to be clustered in specific regions, most of which make known contributions to catalytic activity. The vanillate analogs m-anisate, m-toluate, and 4-hydroxy-3,5-dimethylbenzoate are substrates of the enzyme and weakly inhibit the metabolism of vanillate by wild-type Acineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
27
0
2
Order By: Relevance
“…5,7,9) In a preliminary experiment, when a lysate was prepared from Streptomyces sp. NL15-2K cells exhibiting vanillate demethylase activity, activity of the enzyme was not detected in the lysate regardless of supplementation with cofactors such as reduced nicotinamide adenine dinucleotide (NADH) and reduced nicotinamide adenine dinucleotide phosphate (NADPH).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,9) In a preliminary experiment, when a lysate was prepared from Streptomyces sp. NL15-2K cells exhibiting vanillate demethylase activity, activity of the enzyme was not detected in the lysate regardless of supplementation with cofactors such as reduced nicotinamide adenine dinucleotide (NADH) and reduced nicotinamide adenine dinucleotide phosphate (NADPH).…”
Section: )mentioning
confidence: 99%
“…have been determined in studies using cell-free extracts or recombinant Escherichia coli cells transformed with the vanillate demethylase gene. [7][8][9] Vanillate demethylase from P. testosteroni has a broad substrate range and shows activity towards m-and p-anisate in addition to vanillate, 7) whereas the enzyme from P. fluorescens is inactive toward p-anisate. 8) Similarly, although vanillate demethylase from Acinetobacter sp.…”
mentioning
confidence: 99%
“…It might be concluded that an objective analysis of how structure influences function is achieved more readily by confessions of ignorance guiding investigations using random mutagenesis than by assumptions of knowledge determining targets for site-directed mutagenesis. Particularly gratifying was success in the identification of essential residues in vanillate demethylase, a membrane-associated enzyme that has resisted purification (25). Combination of A. baylyi natural transformation with PCR mutagenesis and appropriate selection also made it possible to select strains that had altered binding targets for repressors (21) and altered substrate specificity for an enzyme (6).…”
Section: Acinetobacter Re-entersmentioning
confidence: 99%
“…strain ADP1. These investigations have given valuable insight into structure-function relationships in these proteins (7,15,16,17,24,29). However, when we applied the random PCR mutagenesis approach to pcaK, a gene encoding a protocatechuate transporter belonging to the ubiquitous major facilitator superfamily (28), evidence of bias in the mutant collection was observed.…”
mentioning
confidence: 99%
“…A merit of the procedure is its objectivity because mutations are identified on the basis of phenotypic variation. No presumptions are brought to bear on the identification of targets for mutagenesis, so amino acid contributions that might not have been predicted can be characterized (7,10,24). Nevertheless, the procedure must be regarded with caution because not all nucleotide substitutions are made with equal probability during PCR amplification (34).…”
mentioning
confidence: 99%